2016
DOI: 10.1016/j.mri.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal allografts function early after transplantation using intravoxel incoherent motion and arterial spin labeling MRI

Abstract: Combined IVIM and ASL MRI can better evaluate the diffusion and perfusion properties for allografts early after kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 29 publications
5
54
0
Order By: Relevance
“…DWI is a powerful MRI technique used for imaging molecular movement or diffusion that reflects changes in microstructure of biological tissues . Previous studies have confirmed that IVIM‐DWI can be used to assess renal function . However, renal pathology plays an important role in guiding therapy and follow‐up of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI is a powerful MRI technique used for imaging molecular movement or diffusion that reflects changes in microstructure of biological tissues . Previous studies have confirmed that IVIM‐DWI can be used to assess renal function . However, renal pathology plays an important role in guiding therapy and follow‐up of CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…IVIM‐DWI has been used to detect dysfunction of transplanted kidney in human studies, and evaluate renal fibrosis using animal models . Moreover, cortical D, D*, and f showed a positive correlation with estimated glomerular filtration rate (eGFR) in transplanted kidneys …”
mentioning
confidence: 99%
“…However, Artz et al [51] reported a poor reproducibility of medullar perfusion measurements in patients with transplanted kidneys. Perfusion measurements correlated positively with GFR values in recipients [54]. Moreover, combined measurements of RBF by ASL and GFR seem to be good predictors of loss of renal reserve in potential donors [55].…”
Section: Asl Mri In the Assessment Of Kidney Pathologiesmentioning
confidence: 99%
“…Clinically, radiologists and nephrologists appreciate the utility of the DWI-MRI technique in assessing renal physiological or pathological changes. Previous studies have shown that the DWI technique is a sensitive method for detecting renal function in patients with chronic kidney disease [9], evaluating renal allografts function [10], assessing the severity of renal pathology, and guiding therapy for patients with CKD [11]. To the best of our knowledge, only two studies focused on the use of DWI-MRI in LN have been published.…”
Section: Introductionmentioning
confidence: 99%